Kidnap [videorecording (DVD)] - Berry, Halle; Correa, Sage, 2007-; McGinn, Chris (Universal Pictures Home Entertainment, 2017)
A typical afternoon in the park turns into a nightmare for single mom Karla Dyson when her son suddenly disappears. Without a cell phone and knowing she has no time to wait for police help, Karla jumps in her own car and sets off in pursuit of the kidnappers. Karla will stop at nothing to recover her kidnapped son.